The Role of Organizational Culture as a Mediating Variable on Employee Performance in the MSME Business World in Semarang City - Arfah, Susilo Ariana; Firdaus; Nurhayati; Haerudin (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
Small Medium Enterprises (SMEs) have an important role in national economic development. This is an important pillar for further national economic development. This research aims to look at the role of organizational culture in bridging work simplification and accelerated change in employee performance in Semarang City SEMs, both directly and indirectly. This research used a 1-5 scale questionnaire for 100 respondents and was processed using AMOS PLS. The results of this research show that causality between work simplification and accelerated change in employee performance does not have a significant effect, but this research also proves that the role of organizational culture can bridge deviations in this research, the existence of organizational culture as a mediator can improve performance. Employees at SEMs in Semarang City, in this research the results also show that mediating variable plays its full role.